Hormona folículo estimulante (FSH) vía epidural como herramienta para simplificar los protocolos de superovulación en vacas donantes de embriones - Carabajo Mendieta, Jelly Daniela (2024)
The objective of this research was to evaluate the impact of the combined administration of FSH via epidural and intramuscular routes with the purpose of optimizing superovulation protocols in crossbred embryo donor cows. For its execution, an experimental design was determined where 8 Bos Indicus crossbred cows were selected with an average weight of 400-450 kg, body condition of 2.5 without reproductive complications. Two comparative treatments were used: T1 (n=4; conventional) received 12 ml of FSH intramuscularly in 8 decreasing doses, in the morning and afternoon, in T2 (n=4; epidural route) 10 ml of FSH was administered in one single dose epidurally on day 4 and an intramuscular booster (2ml) on day 7. The response to the superovulation process, number of preovulatory follicles (T1=7.25 ± 1.91 vs T2=8.75 ± 3.11), corpus luteum (T1=5.38 ± 1.60 vs T2=4.13 ± 0.99) and embryonic structures (T1=5.25 ± 3.69 vs T2=1 ± 1.41) were similar for both groups (p>0.05). However, there was no significant increase (p>0.05) in the number of structures obtained, but rather in their quality; furthermore, the percentage of embryos in different stages of development did not differ between groups (p>0.05). It is concluded that follicle stimulating hormone (FSH) administered epidurally plus an intramuscular booster produces a response similar to the conventional protocol, however, the number of transferable embryos is lower